Focus Group Discussion Masalah Pertanian dan Pemberdayaan Masyarakat melalui Penanaman Pohon Bambu di Salingka Kampus Universitas Andalas - Zahlul Ikhsan; Hidrayani Hidrayani; Winarto Winarto; Yusniwati Yusniwati; Roza Yunita; Nofrita Sandi; Sri Wahyuni; Nofialdi Nofialdi; Reflinaldon Reflinaldon (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Land conditions in Sungkai, Padang City, have slopes and high rainfall. The causes low water absorption capacity. For this reason, it is necessary to plant plants that can help increase water absorption, one of which is bamboo plants. This activity was carried out on November 6, 2021, to empower the community of farmer groups in the Andalas University campus with a focus group discussion on agricultural issues and planting bamboo trees. The activity consists of four stages: preparation, counselling/socialization, focus group discussion, and field practice. There are five main problems to solve. The issues found are 1) how to handle flooding in the river; 2) how to control plant-disturbing organisms without using chemicals; 3) new land clearing methods so as not to damage the environment; 4) how to obtain and treat good seeds and seedlings before planting, and 5) farmer group dynamics and their resolution. Planting bamboo is one of the steps to deal with the problem of flooding. Bamboo has a very tight, broad, and strong root system to strengthen the soil structure and withstand water runoff. Bamboo plants can also become new hosts of pests that damage cultivated plants. The service team synergizes with extension workers to understand bamboo, which can be an alternative in sustainably conserving soil and water.